المال وعلاقته بالإستخلاف في الأرض من المنظور القرآني - مسكري، عامر بن سعيد بن سليمان (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah al-Jami'ah al-Islamiyah al-'Alamiyah bi- Maliziya, 2006)
The aim of this study is three folds: first to show the Qur’anic perspective towards money/wealth and its importance and impact on achieving the istikhlaf on the Earth. Second, to show that money is considered from the sources of power that Muslims should possess to develop the ummah in a comprehensive way. Third, to reveal the negative perspective towards money on the individual and society. The methodology that is adopted in this study is an inductive approach by following the Qur’anic verses that dealt with the topic as well as the descriptive analytical approaches to show the Qur’anic view from money then analyzing the Qur’anic verses with the aim of concluding with the Qur’anic perspective towards money and the application of this perspective in our contemporary life. The study arrived to the following result. The Qur’an gave money a priority and considered it as very important for people. Man is given money and is asked to gain it and investing it in halal (permissible) ways in trade, agriculture, and industry. Man is asked to spend money in the welfare of people. Qur’an put the rules and laws the keeps money from spoil or waste or theft. Qur’an also prohibited wrong treatment and taking the money of the others forcibly or without right. The negative perspective towards money reflected itself on the individual and the society by separating life from hereafter and thus misery, cheating, and poverty spread. This contributed in the weakness of the Ummah in all the fields. Finally, the Qur’anic perspective is a balanced one where Qur’an asked faithful people to work properly in this life to go to the hereafter by making every work as worship as long as the work is a legitimate one and the intention is to be closer to Allah subhanahu wata'ala.